STRUKTUR KOMUNITAS HYMENOPTERA PARASITOID PADA TUMBUHAN LIAR DI SEKITAR PERTANAMAN PADI DI DAERAH ALIRAN SUNGAI (DAS) CIANJUR, JAWA BARAT - Yaherwandi, S. Manuwoto, D. Buchori, P. Hidayat, dan L.B. Prasetyo. (Universitas Lampung, 2008)
Hymenoptera Parasitoid Community Structure on Non-crops Vegetation Around Rice fields in Cianjur Watershed, West Java. Hymenoptera parasitoids have an important role in agroecosystem because of their ability in suppressing pest population. Their presence in the field is seen as the key to agricultural ecosystem. Their presence can be influenced by the availability of non-crop vegetation. Some adult Hymenoptera parasitoids require food in the form of pollen and nectar of wild flowers to ensure effective reproduction and longevity. The objective of this research was to study Hymenoptera parasitoid communities in non-crop vegetation around rice fields at Cianjur Watershed. Samplings were conducted at three different landscape, i.e. Nyalindung, Gasol and Selajambe West Java. Insects were sampled by two trapping techniques (farmcop and sweep net) in two lines of transect for each landscape. A total of 257 species from 25 families of Hymenoptera parasitoids were collected in non-crop vegetation at Cianjur Watershed. Landscape structure, flowering vegetation, and pesticide application affected the species richness, diversity and evenness of Hymenoptera parasitoid in non-crop vegetation.